2020
DOI: 10.1177/0003319720951411
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Role of Serum 25-Hydroxy Vitamin D Level on Coronary Heart Disease Risk With Stratification Among Patients With Type 2 Diabetes Mellitus

Abstract: We investigated the role of vitamin D on glycemic regulation and cardiac complications in patients with type 2 diabetes mellitus (T2DM). A total of 1139 patients (49.3% males vs 50.7% females) were included. Information on sociodemographic lifestyle, family history, blood pressure (BP), and coronary heart disease (CHD) complications was collected. Significant differences were found between males and females regarding age-groups ( P = .002), body mass index (BMI; P = .008), physical activity ( P = .010), sheesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(89 reference statements)
0
3
0
1
Order By: Relevance
“…Large-scale epidemiological studies reported that hypertension prevalence is 33.7%, and diabetes mellitus and pre-diabetes prevalence is 13% in Turkish adults. [18,19] These high frequencies of diabetes and hypertension in the Turkish population might affect our study population. Therefore, it can be the reason for the statistical indifference for those variables between survivors and non-survivors.…”
Section: Discussionmentioning
confidence: 95%
“…Large-scale epidemiological studies reported that hypertension prevalence is 33.7%, and diabetes mellitus and pre-diabetes prevalence is 13% in Turkish adults. [18,19] These high frequencies of diabetes and hypertension in the Turkish population might affect our study population. Therefore, it can be the reason for the statistical indifference for those variables between survivors and non-survivors.…”
Section: Discussionmentioning
confidence: 95%
“…10 Evidências sugerem que a deficiência de 25-hidroxivitamina D (25(OH)D) está significativamente associada ao aumento do risco cardiovascular. 11,12 A avaliação do risco cardiovascular tem tido papel fundamental na prevenção de DCVs. As estimativas de risco podem contribuir na conscientização da população sobre as DCVs, motivando a adesão às mudanças de estilo de vida, ou indicando a introdução do tratamento da pressão arterial elevada e de outros medicamentos.…”
Section: Introductionunclassified
“…[8,9] Some studies have reported that circulating concentrations of vitamin D were low in subjects with T2DM and IHD. [10,11] For instance, a study in patients with T2DM who had a history of IHD found a strong inverse relation between low vitamin D concentrations and prevalent coronary or peripheral cardiovascular disease. [12] The beneficial effects of vitamin D administration on indexes of insulin production and resistance, lipid profiles, and biomarkers of inflammation and oxidative stress may be mediated through its impact on activating insulin receptor expression, the downregulation of cytokine generation, and lower production of parathyroid hormone.…”
Section: Introductionmentioning
confidence: 99%